Awareness of the patterns of delivery in urban slums of Ahmedabad city - Girish Patel, Shailee; Patel, Rajkumar Pareshbhai; Patel, Niral Rajnibhai; Patel, Khush (International Journal Of Community Medicine And Public Health, 2018)
Background: The field of medicine has changed over the years owing to the constant scientific advances and research. From a time when spontaneous vaginal delivery used to be the norm, to now, where the rates of Caesarean deliveries seemed to be increasing, obstetric care has evolved considerable. Several healthcare initiatives and schemes have been framed for the betterment of the female reproductive health in recent times. It is important to understand both medical as well socio-cultural factors that have caused this increase in the caesarean births. This study was conducted keeping in mind this trend and to find out the level of awareness regarding patterns of deliveries that factors into this trend. Methods: Cross – sectional study was done in women residing in an urban slum of Ahmedabad in February 2014. 68 consenting female were randomly selected for the study from the slum of ‘Madi no Kuvo’. Results: Majority of females (69%) were from age group 20-30 years. With a total number of 123 deliveries counted within the 68 female interviewed 67% were normal vaginal deliveries. 63% of surveyed women had deliveries at government hospital as civil hospital is nearby localities surveyed and cost incurrence was there in about half of deliveries while 27 % deliveries occurred at private hospitals. Conclusions: Majority of women would prefer to have normal delivery whenever it is possible. Majority of people were unaware about different government schemes to help females during pregnancy.